PENGEMBANGAN VIDEO PEMBELAJARAN MENGGUNAKAN APLIKASI CAPCUT PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS 8 SMP/MTS TENTANG SUJUD - Mochammad Ilyas Pratama; Shokhibul Arifin; Ika Puspitasari (Kuttab : Jurnal Ilmu Pendidikan Islam, 2023)
In the learning process, the existence of media is an absolute must. But until now, many educational institutions still need to maximize learning media. This study aimed to determine the level of product validity in the form of learning videos that the researchers had made. This research uses the Research and Development (R&D) method and applies the 4D development model; define, design, development Â and dissemination. The validation test data concluded that: 1) the percentage obtained from material expert validation 1 was 87% with high-intensity score criteria. In comparison, the material expert validation test 2 was 78% and received high score criteria. 2) the percentage of the results of the media expert validation test 1 is 90.2%, with the criteria for a high-intensity score. In comparison, the media expert validation test 2 gets a percentage of 98%, with the criteria for a high-intensity score. Based on the results of the module and media validation tests, it can be concluded that the learning video media for prostration material for class 8 semester 2 is feasible to use